Festival Religius Kultural Wisata Warisan: Mauluik Gadang dan Pengembangan Destinasi Berbasis Komunitas di Padang Pariaman - Faisal Hidayat; Miftahurrahmah (Program Studi Pariwisata Syariah - UIN Sjech M. Djamil Djambek Bukttinggi, 2025)
Religious and cultural festivals are increasingly positioned as important tools for diversifying tourism products and supporting the sustainability of intangible cultural heritage (ICH) in various predominantly Muslim destinations. This article examines Mauluik Gadang, a large-scale celebration of the Prophet's birthday that was recently institutionalized as a district-level festival in Padang Pariaman, West Sumatra, as an example of heritage tourism development rooted in Minangkabau Islamic traditions. Using a mixed methods design with a qualitative orientation, this study combines visitor surveys, semi-structured interviews with community leaders, religious scholars, local government officials, women's and youth groups, and three days of participatory observation during the festival. The analysis is based on an integrated framework linking the experience economy and memorable tourism experiences (MTEs), community-based tourism and social capital, and authenticity/place attachment in WBTb tourism. Findings indicate that visitors are simultaneously motivated by religious impulses, cultural nostalgia, and social experience motives. Rituals such as marhaban, Syarafal Anam, badikie, and makan bajamba, combined with market activities and creative performances, produced layered experiences that combined sacredness and a festive atmosphere. The festival strengthens social cohesion, encourages local micro-enterprises and MSMEs, and reinforces place attachment for residents and migrants, but at the same time raises tensions related to commodification, visitor density, and the protection of sacred meanings. This study contributes to the literature on festivals and religious tourism by interpreting Mauluik Gadang as a hybrid sacred tourism space where WBTb continues to be negotiated through state-community collaboration. Practically, this article presents policy and management implications for local governments and community organizations seeking to develop WBTb-based heritage destinations in Indonesia and other Muslim-majority contexts, while maintaining religious and cultural integrity Festival religiuskultural semakin diposisikan sebagai instrumen penting untuk mendiversifikasi produk pariwisata dan menopang keberlanjutan warisan budaya takbenda (WBTb) di berbagai destinasi mayoritas Muslim. Artikel ini mengkaji Mauluik Gadang perayaan Maulid Nabi skala besar yang barubaru ini dilembagakan sebagai festival tingkat kabupaten di Padang Pariaman, Sumatera Barat sebagai kasus pengembangan wisata warisan yang berakar pada tradisi Islam Minangkabau. Dengan menggunakan desain mixed-methods yang berorientasi kualitatif, penelitian ini memadukan survei pengunjung, wawancara semiterstruktur dengan tokoh komunitas, ulama, pemerintah daerah, kelompok perempuan dan pemuda, serta pengamatan partisipan selama tiga hari penyelenggaraan festival. Analisis didasarkan pada kerangka terintegrasi yang menghubungkan ekonomi pengalaman dan memorable tourism experiences (MTEs), pariwisata berbasis komunitas dan modal sosial, serta otentisitas/kelekatan tempat dalam pariwisata WBTb. Temuan menunjukkan bahwa pengunjung termotivasi secara simultan oleh dorongan religius, nostalgia kultural, dan motif social eksperiensial. Ritualitas seperti marhaban, Syarafal Anam, badikie, dan makan bajamba, yang berpadu dengan aktivitas bazar dan pertunjukan kreatif, menghasilkan pengalaman berlapis yang menggabungkan kesakralan dan suasana pesta. Festival ini memperkuat kohesi sosial, mendorong usaha mikro dan UMKM lokal, serta meneguhkan kelekatan tempat bagi warga maupun perantau, namun sekaligus memunculkan ketegangan terkait komodifikasi, kepadatan pengunjung, dan perlindungan makna sakral. Studi ini berkontribusi pada literatur festival dan pariwisata religi dengan memaknai Mauluik Gadang sebagai ruang hibrid sacral turistik di mana WBTb terus dinegosiasikan melalui kolaborasi komunitas negara. Secara praktis, artikel ini menyajikan implikasi kebijakan dan manajerial bagi pemerintah lokal dan organisasi komunitas yang ingin mengembangkan destinasi warisan berbasis WBTb di Indonesia dan konteks mayoritas Muslim lainnya, dengan tetap menjaga integritas religius dan kultural.